Effect of Wage Level, Wage Mechanism and Number of Family Members on the Welfare of Sanitary Officers at the Mandailing Natal District Environmental Service - Rina Sari; Sri Ramadhani; Muhammad Syahbudi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of wage levels, remuneration mechanisms and number of family members on the welfare of cleaning staff at the Mandailing Natal Regency Environmental Service. The dependent variable is welfare, while the independent variables are the level of wages, the mechanism of wages and the number of family members. This study uses primary data, with multiple linear regression data analysis method using SPSS 15. The research respondents were 52 people, the sampling method used was Simple Random Sampling technique. Based on the results of the first hypothesis test, it is known that the significant value of the wage level is 0.012 (sig < 0.05) with a t count value of 2.613 > 2.010 (t arithmetic > t table). The second hypothesis test shows a significant wage mechanism of 0.000 (sig < 0.05) with a t count value of 14.345 > 2.010 (t arithmetic > t table). And based on the third hypothesis test, it is known that the significant value of the number of family members is 0.000 (sig < with t value -5.050 < 2.010 (t count < t table). Based on the results of the fourth hypothesis test, it is known that the significant value is 0.000 (sig < 0.05) with a F count 287,670 is greater than F table 2.80 (F count > F table).The results of this study indicate Wage Level, Wage Mechanism and Number of Family Members simultaneously have a significant effect on welfare.